Governança da cadeia produtiva da ovinocultura no Rio Grande do Sul: estudo de caso à luz dos custos de transação e produção - Viana, João Garibaldi Almeida (2008)
Sheep production in Rio Grande do Sul has been through a rearrangement period after the crisis faced at the beginning of the 1990s. The recent increase of demand for quality sheep meat has generated a farmers organization process. These initiatives improved chain coordination and led to new governance structures. The objective of this work is to study the governance of the sheep productive chain in Rio Grande do Sul, evaluating the impact of transaction and production costs on the establishment of transaction arrangements. Seven sheep farmers from three municipalities in the south of Rio Grande do Sul participated in the research, in addition to three slaughterhouse companies, through which the producers commercialized their products. The project adopted a case study methodology. This research used a combination of a quantitative approach in the formulation of the production costs and economical indicators, and a qualitative approach in the survey of transaction costs and description of the productive chain. Two governance structures in the industry-producer relationship were identified: the classical market arrangement, which deals with low transaction cost relationships; and the horizontal coordination arrangement, established to deal with asset transactions of greater specificity and frequency and also control opportunistic behavior. The variable costs, such as labor and rough input costs, together with opportunity costs represented the largest share of the total cost. Sheep production is a profitable activity, as indicated by the farmer operational income. The unitary cost variations among the producers were due to the different values obtained from the production acquired. The production costs for the development of more specific assets and the transaction costs present in the relations between parts were the reasons for the formation of horizontal coordination.